Ex-Dividend Arbitrage in Option Markets - Hao, Jia; Kalay, Avner; Mayhew, Stewart (Review of Financial Studies, 2010)
[We examine the behavior of call options surrounding the underlying stock's ex-dividend date. The evidence is inconsistent with the predictions of a rational exercise policy; a significant fraction of the open interest remains unexercised, resulting in a windfall gain to option writers. This triggers a sophisticated trading scheme that enables short-term traders to receive a significant fraction of the gains. The trading scheme inflates reported volume and distorts its traditional relations to liquidity. The dramatic increases in the volume of trade on the last cum-dividend day are facilitated by limitations on transaction costs passed by the various option exchanges.]